Exploring the effects of habituation and scent in first-person 360-degree videos on consumption behavior - Li, Benjamin Junting (2023)
Although immersive virtual environments can influence food-related thoughts, emotions and behavior, the influence of repeated exposure to food cues in such environments has rarely been explored. This study seeks to understand if habituation, a decrease in one's physiological and behavioral response that results from repeated simulation, can take place while repeatedly watching 360-degrees of food being consumed. The influence of scent as an olfactory cue is further explored, based on past research on embodied cognition. In Study One (n = 42), participants who viewed 30 repetitions of someone eating an M&M ate significantly fewer M&Ms than those who viewed three repetitions. Study Two (n = 114) used a 2 (behavior: eating M&M/inserting a coin) × 2 (repetitions: 3/30) between-subjects experiment to confirm that results from Study One were due to habituation of the consumption video, finding that there were only significant differences between repetitions in the M&M condition. Finally, Study Three (n = 161) comprised a 2 (repetition: 3/30) × 2 (scent: present/absent) between-subjects experiment. Participants in the 30-repetition condition and those in the scent-present condition ate significantly fewer M&Ms respectively, but no interaction effects were found. The theoretical and practical implications of these findings are discussed.